(untitled) (Comprehensive Journal of Science, 2025)
This study examines phonetic preference in Arabic through points of articulation and phonetic features and their impact on lexical and contextual meaning. It argues that variation in speech performance does not alter the overall phonological system, which remains a key reference for interpreting linguistic phenomena. The study outlines consonants and vowels and describes major features (e.g., voicing vs. devoicing, plosiveness vs. frication, elevation and emphaticness) to build criteria for phonetic strength and weakness. It then links these criteria to meaning through lexical examples showing how sound differences correlate with semantic nuance. An applied analysis of selected verses from Sūrat al-Burūj demonstrates how sound structure aligns with contextual meaning, especially in expressions of oath, grandeur, and warning. The study concludes that articulatory and feature-based patterns shape sound meaning and enhance verbal craftsmanship, supporting clearer, more effective expression.